EPISTEMOLOGI HERMENEUTIKA - Hayatun Nufus (PT. Saha Kreasi Indonesia, 2025)
Hermeneutic epistemology is a branch of the philosophy of science that focuses on the process of knowledge through understanding and interpretation, rather than mere empirical observation or logical rationality. In the Western philosophical tradition, hermeneutics developed from Schleiermacher and Dilthey, who positioned it as a method for understanding texts, to Heidegger and Gadamer, who viewed it as the ontological foundation of human existential understanding. Ricoeur later enriched hermeneutics with a phenomenological approach to uncover the meanings of symbols and narratives. In the context of scholarship in Indonesia, hermeneutic epistemology has become relevant because it offers an interpretive paradigm that emphasizes dialogue between the text, the reader, and the socio-historical context. This approach has made significant contributions to the development of Islamic studies, particularly in Qur’anic interpretation, education, and the philosophy of science, ensuring that they do not become trapped in empirical reductionism but instead remain contextual, reflective, and humanistic.